Difference between revisions of "1984 AIME Problems/Problem 5"
Brandonyee (talk | contribs) (→Solution 10) |
|||
(4 intermediate revisions by 3 users not shown) | |||
Line 13: | Line 13: | ||
== Solution 4 == | == Solution 4 == | ||
− | We can change everything to a common base, like so: <math>\log_8{a} + \log_8{b^3} = 5,</math> <math>\log_8{b} + \log_8{a^3} = 7.</math> We set the value of <math>\log_8{a}</math> to <math>x</math>, and the value of <math>\log_8{b}</math> to <math>y.</math> Now we have a system of linear equations: <cmath>x + 3y = 5,</cmath> <cmath>y + 3x = 7.</cmath> | + | We can change everything to a common base, like so: <math>\log_8{a} + \log_8{b^3} = 5,</math> <math>\log_8{b} + \log_8{a^3} = 7.</math> We set the value of <math>\log_8{a}</math> to <math>x</math>, and the value of <math>\log_8{b}</math> to <math>y.</math> Now we have a system of linear equations: <cmath>x + 3y = 5,</cmath> <cmath>y + 3x = 7.</cmath> Now add the two equations together then simplify, we'll get <math>x+y=3</math>. So <math>\log_8{ab} = \log_8{a} + \log_8{b} = 3</math>, <math>ab = 8^3 = \boxed{512}</math> |
== Solution 5 == | == Solution 5 == | ||
Line 39: | Line 39: | ||
== Solution 8 == | == Solution 8 == | ||
− | <math>\ | + | Adding both of the equations, we get |
− | < | + | <cmath>\log_8{ab} +2\log_4{ab}=12</cmath> |
+ | Furthermore, we see that <math>\log_4 {ab}</math> is <math>\frac{3}{2}</math> times <math>\log_8 {ab}.</math> Substituting <math>\log_8 {ab}</math> as <math>x,</math> we get <math>x+3x=12,</math> so <math>x=3.</math> Therefore, we have <math>\log_8 {ab} = 3,</math> so <math>ab= 8^3=\boxed{512}</math> ~ math_comb01 | ||
+ | |||
+ | == Solution 9 == | ||
+ | |||
+ | Change all equations to base 64. We then get: | ||
+ | <cmath> \log_{64}(a^2) + \log_{64}(b^6) = 5 </cmath> | ||
+ | and | ||
+ | <cmath> \log_{64}(b^2) + \log_{64}(a^6) = 7. </cmath> | ||
+ | |||
+ | Using the property \(\log(a) + \log(b) = \log(ab)\), we get: | ||
+ | <cmath> \log_{64}(a^2b^6) = 5 </cmath> | ||
+ | and | ||
+ | <cmath> \log_{64}(a^6b^2) = 7. </cmath> | ||
+ | |||
+ | Then: | ||
+ | <cmath> a^2b^6 = 64^5 </cmath> | ||
+ | and | ||
+ | <cmath> a^6b^2 = 64^7. </cmath> | ||
+ | |||
+ | Simplifying, we have: | ||
+ | <cmath> ab^3 = 8^5 </cmath> | ||
+ | and | ||
+ | <cmath> a^3b = 8^7. </cmath> | ||
+ | |||
+ | Substituting and solving, we get: | ||
+ | <cmath> a = 8^2 </cmath> | ||
+ | and | ||
+ | <cmath> b = 8. </cmath> | ||
+ | |||
+ | Then: | ||
+ | <cmath> ab = 8^3 = 512. </cmath> | ||
+ | |||
+ | == Solution 10 == | ||
+ | |||
+ | Given: | ||
+ | - <math>\log_8 a + \log_4 b^2 = 5</math> | ||
+ | - <math>\log_8 b + \log_4 a^2 = 7</math> | ||
+ | |||
+ | We set up a system by subtracting 2 from the second equation to make both equal to 5: | ||
+ | - <math>\log_8 a + \log_4 b^2 = 5</math> | ||
+ | - <math>\log_8 b + \log_4 a^2 - 2 = 5</math> | ||
+ | |||
+ | Setting these equal: | ||
+ | <math>\log_8 a + \log_4 b^2 = \log_8 b + \log_4 a^2 - 2</math> | ||
+ | |||
+ | Using the property <math>\log_4 x^2 = 2\log_4 x</math>: | ||
+ | <math>\log_8 a + 2\log_4 b = \log_8 b + 2\log_4 a - 2</math> | ||
+ | |||
+ | Converting to base 2, where <math>\log_8 x = \frac{\log_2 x}{3}</math> and <math>\log_4 x = \frac{\log_2 x}{2}</math>: | ||
+ | <math>\frac{\log_2 a}{3} + 2\cdot\frac{\log_2 b}{2} = \frac{\log_2 b}{3} + 2\cdot\frac{\log_2 a}{2} - 2</math> | ||
+ | |||
+ | Simplifying: | ||
+ | <math>\frac{\log_2 a}{3} + \log_2 b = \frac{\log_2 b}{3} + \log_2 a - 2</math> | ||
+ | |||
+ | Multiplying through by 6 to eliminate fractions: | ||
+ | <math>2\log_2 a + 6\log_2 b = 2\log_2 b + 6\log_2 a - 12</math> | ||
+ | |||
+ | Rearranging: | ||
+ | <math>2\log_2 a - 6\log_2 a + 6\log_2 b - 2\log_2 b = -12</math> | ||
+ | <math>-4\log_2 a + 4\log_2 b = -12</math> | ||
+ | <math>\log_2 b - \log_2 a = -3</math> | ||
+ | |||
+ | Therefore: | ||
+ | <math>\log_2\left(\frac{b}{a}\right) = -3</math> | ||
+ | <math>\frac{b}{a} = \frac{1}{8}</math> | ||
+ | <math>b = \frac{a}{8}</math> | ||
+ | |||
+ | From the first original equation: | ||
+ | <math>\log_8 a + \log_4 b^2 = 5</math> | ||
+ | |||
+ | Substituting <math>b = \frac{a}{8}</math>: | ||
+ | <math>\log_8 a + \log_4 \left(\frac{a}{8}\right)^2 = 5</math> | ||
+ | <math>\log_8 a + \log_4 \left(\frac{a^2}{64}\right) = 5</math> | ||
+ | <math>\log_8 a + \log_4 a^2 - \log_4 64 = 5</math> | ||
+ | |||
+ | Since <math>\log_4 64 = \log_4 4^3 = 3</math>: | ||
+ | <math>\log_8 a + \log_4 a^2 - 3 = 5</math> | ||
+ | <math>\log_8 a + \log_4 a^2 = 8</math> | ||
+ | |||
+ | Now we have: | ||
+ | - <math>\log_8 a + \log_4 a^2 = 8</math> (derived) | ||
+ | - <math>\log_8 b + \log_4 a^2 = 7</math> (given) | ||
+ | |||
+ | Subtracting: | ||
+ | <math>\log_8 a - \log_8 b = 1</math> | ||
+ | <math>\log_8\left(\frac{a}{b}\right) = 1</math> | ||
+ | <math>\frac{a}{b} = 8</math> | ||
+ | |||
+ | This confirms our earlier finding that <math>b = \frac{a}{8}</math>, so <math>a = 8b</math>. | ||
+ | |||
+ | Substituting this back into the first original equation: | ||
+ | <math>\log_8 (8b) + \log_4 b^2 = 5</math> | ||
+ | <math>\log_8 8 + \log_8 b + \log_4 b^2 = 5</math> | ||
+ | <math>1 + \log_8 b + \log_4 b^2 = 5</math> | ||
+ | <math>\log_8 b + \log_4 b^2 = 4</math> | ||
+ | |||
+ | From the second original equation: | ||
+ | <math>\log_8 b + \log_4 (8b)^2 = 7</math> | ||
+ | <math>\log_8 b + \log_4 (64b^2) = 7</math> | ||
+ | <math>\log_8 b + \log_4 64 + \log_4 b^2 = 7</math> | ||
+ | <math>\log_8 b + 3 + \log_4 b^2 = 7</math> | ||
+ | <math>\log_8 b + \log_4 b^2 = 4</math> | ||
+ | |||
+ | Thus both equations yield the same constraint: <math>\log_8 b + \log_4 b^2 = 4</math> | ||
+ | |||
+ | Converting to base 2: | ||
+ | <math>\frac{\log_2 b}{3} + \frac{2\log_2 b}{2} = 4</math> | ||
+ | <math>\frac{\log_2 b}{3} + \log_2 b = 4</math> | ||
+ | <math>\frac{\log_2 b + 3\log_2 b}{3} = 4</math> | ||
+ | <math>\frac{4\log_2 b}{3} = 4</math> | ||
+ | <math>\log_2 b = 3</math> | ||
+ | |||
+ | Therefore: | ||
+ | <math>b = 2^3 = 8</math> | ||
+ | <math>a = 8b = 8 \cdot 8 = 64</math> | ||
+ | <math>ab = 64 \cdot 8 = 512</math> | ||
+ | |||
+ | The value of <math>ab</math> is <math>\boxed{512}</math>. | ||
+ | |||
+ | ~ brandonyee | ||
== See also == | == See also == |
Latest revision as of 22:42, 6 March 2025
Contents
Problem
Determine the value of if
and
.
Solution 1
Use the change of base formula to see that ; combine denominators to find that
. Doing the same thing with the second equation yields that
. This means that
and that
. If we multiply the two equations together, we get that
, so taking the fourth root of that,
.
Solution 2
We can simplify our expressions by changing everything to a common base and by pulling exponents out of the logarithms. The given equations then become and
. Adding the equations and factoring, we get
. Rearranging we see that
. Again, we pull exponents out of our logarithms to get
. This means that
. The left-hand side can be interpreted as a base-2 logarithm, giving us
.
Solution 3
This solution is very similar to the above two, but it utilizes the well-known fact that Thus,
Similarly,
Adding these two equations, we have
.
Solution 4
We can change everything to a common base, like so:
We set the value of
to
, and the value of
to
Now we have a system of linear equations:
Now add the two equations together then simplify, we'll get
. So
,
Solution 5
Add the two equations to get . This can be simplified with the log property
. Using this, we get
. Now let
and
. Converting to exponents, we get
and
. Sub in the
to get
. So now we have that
and
which gives
,
. This means
so
Solution 6
Add the equations and use the facts that and
to get
Now use the change of base identity with base as 2:
Which gives:
Solving gives,
Solution 7
By properties of logarithms, we know that .
Using the fact that , we get
.
Similarly, we know that .
From these two equations, we get and
.
Multiply the two equations to get . Solving, we get that
.
Solution 8
Adding both of the equations, we get
Furthermore, we see that
is
times
Substituting
as
we get
so
Therefore, we have
so
~ math_comb01
Solution 9
Change all equations to base 64. We then get:
and
Using the property \(\log(a) + \log(b) = \log(ab)\), we get:
and
Then:
and
Simplifying, we have:
and
Substituting and solving, we get:
and
Then:
Solution 10
Given:
-
-
We set up a system by subtracting 2 from the second equation to make both equal to 5:
-
-
Setting these equal:
Using the property :
Converting to base 2, where and
:
Simplifying:
Multiplying through by 6 to eliminate fractions:
Rearranging:
Therefore:
From the first original equation:
Substituting :
Since :
Now we have:
- (derived)
-
(given)
Subtracting:
This confirms our earlier finding that , so
.
Substituting this back into the first original equation:
From the second original equation:
Thus both equations yield the same constraint:
Converting to base 2:
Therefore:
The value of is
.
~ brandonyee
See also
1984 AIME (Problems • Answer Key • Resources) | ||
Preceded by Problem 4 |
Followed by Problem 6 | |
1 • 2 • 3 • 4 • 5 • 6 • 7 • 8 • 9 • 10 • 11 • 12 • 13 • 14 • 15 | ||
All AIME Problems and Solutions |